Etnopedagogy Approach To Science Learning In Sdn 50 City Of Ternate Based On The Local Wisdom Of Rempah North Maluku - Said Hasan; Abdu Mas’ud; Sundari Sundari (Pedagonal : Jurnal Ilmiah Pendidikan, 2021)
Local wisdom-oriented learning in elementary schools in the city of Ternate has not been implemented optimally. In general, schools have implemented thematic learning that should contain local wisdom. Ethnopedagogy is the actualization of learning oriented to the cultivation of local wisdom values. Ethnopedagogic aproach in elementary schools need to be implemented through strategies and innovative learning media that are able to attract students' attention to understand and apply local wisdom. This study aims to integrate Cloves as an identity flora in North Maluku in the implementation of an ethnopedagogic aproach at elementary schools in Ternate. This study uses a qualitative approach with a mixed method of research instruments consisting of observation sheets and questionnaires. Data analysis technique with concurrent triangulation strategy. The results showed that the ethnopedagogical approach implemented through learning activities using cloves as a spice study object in North Maluku was an effective alternative to local wisdom-based learning applied in elementary schools in Ternate city. Through the integration of cloves in an ethnopedagogical approach, it can improve scientific literacy skills and students' learning motivation. This study recommends that the ethnopedagogical approach can be implemented with innovative learning activities based on local wisdom.